Calculation of Runoff Discharge in the Coal Mining Open Pit Mine Conveyance System at PT. Kalimantan Prima Persada Jobsite PELH Kebur Village, West Merapi District, Lahat Regency, South Sumatra Province - Fajar Rofiescha; Rusli HAR; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2024)
PT. Kalimantan Prima Persada Jobsite PELH is a company operating in the field of coal mining contractors. Mining carried out by PT. Kalimantan Prima Persada Jobsite PELH uses the open pit mining method, during the rainy season, the problem that is often found is water. Water that comes from above the ground surface (runoff water) and water that is below the ground surface (ground water). Runoff water and ground water are the main things that must be considered so that they do not disturb and damage the mining location. Therefore, this report was written to find out how much runoff water enters the mining front area. The stages used in calculating runoff water discharge are calculating the catchment area area, calculating planned rainfall data using the Log Pearson III method, calculating rain intensity using the Monnonobe method, calculating runoff water discharge using the rational method. Based on calculations, the catchment area in Pit PE PT was obtained. Kalimantan Prima Persada Jobsite PELH is 540,18 Ha or 5,40 km2, the average daily maximum rainfall in the last 10 years is 547.4 mm/day, planned rainfall is 385,140 mm/day, rain intensity is 80,87 mm/day, and the runoff discharge is 30.204,27 m3/hour.